Quality of Life on Elderly who Lived at Home and at Tresna Werdha Nursing Home - Giovanda Wahyu Andika; Farida Wahyu Ningtyias; Sulistiyani Sulistiyani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2021)
Background: The world's population is currently in an era of aging with the number of elderly people exceeding 7% of the population. This condition will certainly bring positive and negative impacts. It’s needed to pay attention to the elderly, especially on their quality of life. Objective: To determine the differences in the quality of life of the elderly who live with their families in the working area of the Puskesmas Sukorejo and at Jember Tresna Werdha Social Service Unit. Methods: The type of this research was observational analytic using a cross-sectional research design. The study was conducted from January to March 2020. The population in this study amounted to 3472 elderly, consisting of elderly who live in the Tresna Werdha Jember Social Service Unit and live at home with their families in the working area of Sukorejo Community Health Center, Jember. The sample in this study amounted to 100 respondents, consisting of 50 respondents at each research location. The variable studied was the quality of life of the elderly from each place of residence. The data collection instruments included the MMSE questionnaire to assess cognitive impairment in the elderly and the WHOQOL-BREF questionnaire to measure the quality of life in the elderly. The sampling technique used was proportional random sampling. Results: The results showed that the majority of the elderly were aged 60-74 years, most of the elderly were female and never attended school. The majority of the elderly who live at home still have a partner, while those who live in the Social Service have no partner. Chi-square test results showed that there was no difference in the quality of life of the elderly in the physical, psychological, and environmental domains, but there were differences in the quality of life in the social domain. Conclusion: There were no differences in the quality of life in the physical, psychological, and environmental domains, but there were differences in the social domain, among respondents. The elderly who lived at home with their family had a better quality of life in the social domain. Suggestion for the elderly who live at home in the working area of the Sukorejo Community Health Center is to increase positive activities that can entertain themselves and participate in social activities, for the elderly who live at the Tresna Werdha Jember Social Services Unit, it is hoped that they can increase the intensity of good social relations between fellow elderly in homestead and do not close themselves off to the people around them, while for supervisors and caregivers in Tresna Werdha Jember Social Service Unit, it is expected to further improve assistance to the elderly to determine the quality of life of the elderly in each homestead.